Burden of Developmental and Behavioral Problems among Children - A Descriptive Hospital Based Study - Rimal, Hem Sagar; Pokharel, Archana; Saha, Vijay; Giri, Arun; Ghimire, Basudha; Raja, Shiva; Verghease, Bijoy (Journal of Nobel Medical College, 2014)
The child development is a dynamic process that utilizes the genetic potential of the baby to achieve full potential within the context of available environment. Throughout the world, there are growing concerns about developmental, behavioural, social and emotional wellbeing of children. The management of these issues is possible only with an organized approach through a multidisciplinary team Objective: To estimate the prevalence of developmental and behavioral disorders in children. Method: Data were collected from primary caregivers of children presented to a developmental and behavioral pediatrics clinic over a period of 12 months. Standard screening and assessment tools like Strength and Difficulty Questionnaire (SDQ), Spence anxiety scale and Vanderbilt rating scale for ADHD were used. Cases were referred to the Psychiatrist, psychologist, speech therapist and physiotherapist for assessment and management when needed. Results: A total of 85 children with developmental problems presented to our clinic which gives clinic prevalence of 8.5%. There were 51 (60%) of male and 34 (40%) of female. The majority of these children were from Morang district 39 (46%), Sunsari district 13 (15%) and Jhapa District 9 (10.6%). The most common diagnosis were speech and language delay (22.4%), behavioral problems 21.2%, Anxiety disorders 18.8% , cerebral palsy 14.1% and Global developmental delay of 11.8% and several others. The highest number of children i.e 27 (31.8%), were referred to the psychologist/Psychiatrist followed by speech therapist 25 (29.4%) and physiotherapist 21(24.7%). Behavioral modification strategies and CBT were provided to children. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10054 Journal of Nobel Medical College Vol.3(1) 2014; 45-49